1979
DOI: 10.1093/genetics/92.3.823
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC INSTABILITY IN DROSOPHILA MELANOGASTER: THE INDUCTION OF SPECIFIC CHROMOSOME 2 DELETIONS BY MR ELEMENTS

Abstract: We describe the spontaneous induction of deletions by MR elements at the l(2)gl, net, pr and cn loci. The frequent induction of l(2)gl deletions mimics the high frequency of l(2)gl alleles found in wild populations of D. melanogaster. We suggest that these and other data that we present militate far the conclusion that, in the wild, autonomous MR elements occur and function as mutators. We contend that MR elements are not simply the by-products of hybridization between wild and laboratory strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This was especially a consideration since 3 of 5 presumptive en recombinants observed among the progeny of the S-90/cn bw males also appeared to be of Minute phenotype. On the basis of similar observations Green & Shepherd (1979) have suggested that they may be due to short deletions.…”
Section: Experiments and Resultsmentioning
confidence: 85%
“…This was especially a consideration since 3 of 5 presumptive en recombinants observed among the progeny of the S-90/cn bw males also appeared to be of Minute phenotype. On the basis of similar observations Green & Shepherd (1979) have suggested that they may be due to short deletions.…”
Section: Experiments and Resultsmentioning
confidence: 85%